EXPLORING THE RESEARCH OF INTERPROFESSIONAL EDUCATION AND COLLABORATION FOR PATIENT SAFETY: A BIBLIOMETRIC ANALYSIS - Hastami, Yunia; Pamungkasari, Eti Poncorini; Munawaroh, Siti; Hermasari, Bulan Kakanita; Randhita, Amandha Boy Timor; Maftuhah, Atik; Nugroho, Dian; Budiastuti, Veronika Ika (Universitas Gadjah Mada, 2025)
Background: Patient safety is a critical priority in healthcare, aiming to prevent harm and ensure optimal care delivery. Despite the inherent risks in health services, the 'to err is human' paradigm suggests that errors often stem from systemic issues rather than individual failings. Effective patient safety relies heavily on improved system design and the education of healthcare professionals with a focus on safety readiness. Integrating patient safety education into interprofessional education (IPE) frameworks is essential for fostering effective communication and teamwork, which are crucial for reducing structural system errors and enhancing care quality.Aims: To map the research landscape on patient safety and IPE, examining trends, countries, and thematic relationships within the field specifically focusing on how IPE addresses structural system errors in patient safetyMethods: This study conducts a bibliometric analysis using VOS viewer software, the analysis covers publications from January 2000 to July 2024, focusing on data from SCOPUS.Results: Results reveal a growing body of research on patient safety with IPE, highlighting notable simulation-based training and interprofessional collaboration trends. The analysis demonstrates an evolution from individual-focused approaches to system-based interventions. However, there is a clear need for more systematic and culturally nuanced studies, particularly in Southeast Asia, where research is limited.Conclusion: The findings underscore the importance of incorporating patient safety principles within IPE curricula and highlight research gaps, especially in contexts such as Indonesia and other Southeast Asian countries. Future research should address these gaps, explore the impact of IPE on structural system errors across diverse settings, and foster international collaboration to standardize and enhance educational practices in healthcare.